Early sowing enhances genotypic performance in mitigating the risk of wheat blast-induced yield loss: evidence from a 23-year simulation study in Bangladesh - Krupnik, Timothy J.; Fernandes, José M. C.; Pavan, Willingthon; Berton Ferreira, Thiago; Pequeno, Diego N. L.; Hoogenboom, Gerrit; Covert, Virginia L.; Hossain, Khaled; Harun-Or-Rashid, Md.; Islam, Rabiul; Zanatta, Alexandre; Stuerz, Sabine; et al. (Frontiers in Plant Science, 2025)
Wheat is a crucial staple crop in South Asia and faces increasing risks due to interconnected agronomic and climate-related pressures. Wheat blast, caused by Magnaporthe oryzae pathotype Triticum (MoT), presents a persistent threat to wheat production in the region. This study evaluates its impact by analyzing the effects of sowing dates and wheat varieties on irrigated wheat grain yield in Bangladesh, where MoT was first identified in South Asia. A generic disease model (GDM), parameterized to reflect the disease’s characteristics, was used to simulate wheat blast inoculum build-up. The GDM incorporates temperature, relative humidity, and precipitation data to model the fungal life cycle and disease progression. The wheat crop simulation model, DSSAT-Nwheat, was integrated with the GDM to simulate MoT’s life cycle. This coupled model has been embedded into the Geospatial Crop Modeling and Decision Support Tool (GSSAT) to enhance agricultural decision-making. Using a primary dataset for validation and NASA Power reanalysis weather data, the simulated effects of wheat blast on wheat grain yield were analyzed across five sowing dates and four varieties in Bangladesh over a 23-year period from 2001 to 2023. The results indicate that late sowing leads to lower yields and higher disease incidence due to increased atmospheric moisture and temperature. Both model simulations and primary data demonstrated that varietal resistance to wheat blast can significantly mitigate yield losses of wheat. However, in southern Bangladesh, where weather conditions favor the disease, even the most resistant variety, BARI Gom 33, showed yield reductions resulting from wheat blast. These findings highlight the need for long-term breeding programs to develop cultivars suited to hot, humid conditions with high disease pressure, alongside short-term agronomic practices that minimize disease risk through sowing in optimum dates and less susceptible cultivars in Bangladesh.